Static codes [videorecording (DVD)] / CCS Releasing Rad Cine Films Black Wolf Pictures and Vista Film Sales present ; written and directed by David M. Parks. - Manning, Taryn; Duke, Augie; Woodson, Shane; Ferguson, Mike (Leomark Studios, 2025)
An alcoholic podcaster obsessed with his wife's alien abduction experiences a surreal vision and uncovers a government cover-up. In a race against time he must find out the truth before an otherworldly confrontation changes everything.